2020
DOI: 10.3389/fphys.2020.611294
|View full text |Cite
|
Sign up to set email alerts
|

A Novel G542X CFTR Rat Model of Cystic Fibrosis Is Sensitive to Nonsense Mediated Decay

Abstract: Nonsense mutations that lead to the insertion of a premature termination codon (PTC) in the cystic fibrosis transmembrane conductance regulator (CFTR) transcript affect 11% of patients with cystic fibrosis (CF) worldwide and are associated with severe disease phenotype. While CF rat models have contributed significantly to our understanding of CF disease pathogenesis, there are currently no rat models available for studying CF nonsense mutations. Here we created and characterized the first homozygous CF rat mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…Also, the CFTR-null models do not represent the same molecular mechanisms seen in patients with the most common mutations, F508del and G542X, as the random disruption of the gene may lead to unpredictable effects on protein synthesis. Currently, a few F508del and G542X CF animal models have been established, including pig 35 , rat 36,37 , and mouse 38 for the F508del mutation, and mouse 39 and rat 40 for the G542X mutation. The F508del mutants have similar abnormalities as seen in their respective CFTR-null models of the same species, except with less severe damage in some organs due to residual CFTR function 35,36 (Reviewed in 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the CFTR-null models do not represent the same molecular mechanisms seen in patients with the most common mutations, F508del and G542X, as the random disruption of the gene may lead to unpredictable effects on protein synthesis. Currently, a few F508del and G542X CF animal models have been established, including pig 35 , rat 36,37 , and mouse 38 for the F508del mutation, and mouse 39 and rat 40 for the G542X mutation. The F508del mutants have similar abnormalities as seen in their respective CFTR-null models of the same species, except with less severe damage in some organs due to residual CFTR function 35,36 (Reviewed in 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…CF pig models, on the other hand, require a minimum of four offspring to maintain the pregnancy 43 , and normally have 6-10 offspring per pregnancy. G542X CF mice and rats were generated recently 39,40 and exhibit a similar phenotype to their CFTR-null models with no residual CFTR functionality. However, organoids isolated from the intestine of G542X CF mice and epithelial cells isolated from the trachea of G542X CF rats indicated that CFTR protein synthesis could be rescued by G418 antibiotic treatment, thus, partially restoring the CFTR channel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, gene therapies may be a useful treatment option for CF patients carrying nonsense mutations, and the G542X rat model could serve as an important tool for future treatment testing. Multi-agent therapy to augment readthrough could be an alternative approach [ 89 ].…”
Section: Nonsense-mediated Mrna Decay (Nmd) Inhibition By Drugsmentioning
confidence: 99%
“…Nevertheless, rats possess a 76% amino acid sequence identity to h CFTR [ 99 ] and have submucosal glands in the large airways [ 97 , 100 ]. Rat models have also provided the groundwork for exploring new genetic advancements in CF modelling, like the generation of the first G542X CF nonsense mutation rat model with CRISPR-Cas9 [ 101 ], and a new F508del rat models that may be invaluable in the development of therapeutics [ 97 ].…”
Section: Introductionmentioning
confidence: 99%